THE EFFECT OF TOURISM PRODUCT ATTRIBUTES, DESTINATION IMAGE, AND ELECTRONIC WORD OF MOUTH ON THE DECISION TO VISIT LUKUP BADAK RAFTING TOURISM IN TAKENGON - Riska Yulia Putri; Muchsin; Jullimursyida; Khairina AR (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to determine the effect of Tourism Product Attributes, Destination Image and Electronic Word Of Mouth on Visiting Decisions at Lukup Badak Rafting Tourism in Takengon . With the independent variables in this study are Tourism Product Attributes, Destination Image, and Electronic Word Of Mouth (E-WOM) while the dependent variable is the Visiting Decision. This type of research uses a quantitative method, data collection using a questionnaire containing statements in the form of a paper form and given to visitors to the Lukup Badak Rafting tourism with a total of 112 respondents. Data analysis used is validity test, reliability test, classical assumption test, multiple linear regression analysis, research hypothesis, partial (t) test, and coefficient of determination. The program used in analyzing data using the Statistical Package for Social Sciences (SPSS). Based on the results of the study showed that Tourism Product Attributes were proven to have no significant effect, Destination Image and electronic word of mouth were proven to have a positive and significant effect on visiting decisions.